2023
DOI: 10.1186/s12944-023-01881-5
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated lipid metabolism in TMZ-resistant glioblastoma: pathways, proteins, metabolites and therapeutic opportunities

Abstract: Glioblastoma (GBM) is a highly aggressive and lethal brain tumor with limited treatment options, such as the chemotherapeutic agent, temozolomide (TMZ). However, many GBM tumors develop resistance to TMZ, which is a major obstacle to effective therapy. Recently, dysregulated lipid metabolism has emerged as an important factor contributing to TMZ resistance in GBM. The dysregulation of lipid metabolism is a hallmark of cancer and alterations in lipid metabolism have been linked to multiple aspects of tumor biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…This breakthrough enables the identification of lipid distributions and prospective targets for lipid-based therapy. A detailed examination of a GBM patient-derived xenograft (PDX) model, which included mass spectrometry imaging, histology, magnetic resonance imaging, phosphoproteomics, and mRNA sequencing, revealed that the distribution of the EGFR inhibitor erlotinib within intracranial tumors was insufficient to inhibit EGFR tyrosine kinase signaling, despite promising efficacy in vitro studies [ 164 , 165 ].…”
Section: Recent Advancements In Metabolic Reprogramming Of Gbm and Gscsmentioning
confidence: 99%
“…This breakthrough enables the identification of lipid distributions and prospective targets for lipid-based therapy. A detailed examination of a GBM patient-derived xenograft (PDX) model, which included mass spectrometry imaging, histology, magnetic resonance imaging, phosphoproteomics, and mRNA sequencing, revealed that the distribution of the EGFR inhibitor erlotinib within intracranial tumors was insufficient to inhibit EGFR tyrosine kinase signaling, despite promising efficacy in vitro studies [ 164 , 165 ].…”
Section: Recent Advancements In Metabolic Reprogramming Of Gbm and Gscsmentioning
confidence: 99%
“…These foci represent DSBs in a 1:1 ratio and can serve as biomarkers of damage [15][16] . However, the efficacy of TMZ typically diminishes with prolonged treatment time, closely associated with various mechanisms of resistance developed by tumor cells, such as enhanced DNA damage repair and dysregulation of cell cycle checkpoints [17][18][19] . Therefore, exploring novel anti-tumor mechanisms of TMZ and combining it with other strategies may help improve its efficacy and reverse resistance.…”
Section: Introductionmentioning
confidence: 99%